2021
DOI: 10.1093/eurjpc/zwab061.148
|View full text |Cite
|
Sign up to set email alerts
|

An indian clinician outlook on hypertension care during Covid-19 pandemic

Abstract: Funding Acknowledgements Type of funding sources: None. Background Hypertension (HTN) has been found to increase the risk of Covid-19 mortality when compared with normotensives, and those discontinuing the antihypertensive treatment have an additional fatality risk. Objective The survey was carried out to seek the opinion of Indian healthcare practitioners (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this study, the increment is due to individuals at higher risk for HTN were screened, possibly due to fear of higher risk for COVID-19. It may also be due to increased blood pressure due to COVID-19 panic among people at risk for of high blood pressure (32).…”
Section: Methods To Minimize the Impact Of The Pandemic On Hiv/aids S...mentioning
confidence: 99%
“…In this study, the increment is due to individuals at higher risk for HTN were screened, possibly due to fear of higher risk for COVID-19. It may also be due to increased blood pressure due to COVID-19 panic among people at risk for of high blood pressure (32).…”
Section: Methods To Minimize the Impact Of The Pandemic On Hiv/aids S...mentioning
confidence: 99%
“…[20] A survey was conducted by Indian clinicians to find the risk factors causing hypertension during the Covid-19 pandemic and the study showed that tobacco use, obesity and co-morbidities are top three modifiable risk factors for HTN followed by emotional stress, during Covid-19 pandemic. [21] Gordon et al in the year 2021 conducted a large scale study of stress, emotions, and blood pressure in daily life using a digital platform and it concluded that stress is often associated with pathophysiological responses, like BP reactivity, which when experienced repeatedly may be one pathway through which stress leads to poor physical health. [22] In a survey conducted by Kenexa Research Institute, 56% of the women surveyed said that their stress level was reasonable while 26% felt that they were under unreasonable stress.…”
Section: Introductionmentioning
confidence: 99%